Peran Store Atmosphere dan Ketersediaan Produk dalam Membangun Minat Beli Konsumen - Putra Budi Ansori (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
The purpose of this study is to determine the influence of store atmosphere and product availability on consumer purchasing intentions at Mandiri Mart Stores in Pekanbaru City. Store atmosphere has been proven to improve mood, perception of quality, and the urge for consumers to make purchases. This research employs a quantitative descriptive approach. Data were collected through observation, questionnaires, and documentation. The population in this study was 973 consumers who purchased household appliances at Mandiri Mart stores in 2025. A sample of 91 people was selected using a purposive sampling method.. Data analysis was conducted using simple linear regression with the assistance of SPSS version 25. The results from the analysis of multiple linear regression equation was formulated: Y= 13.307 + 0,293X1 + 0,544X2.. The results of the t test (partial test) obtained the value of t arithmetic for Store Atmosphere /X1 (3,388) and product availability/ X2 (5,591) greater than t table of 1,98698, then it has a significant effect on the purchase intention in the Mandiri Mart Pekanbaru. F Test Results (joint test), it is concluded that F count is 34.099> F table 3.10 so that simultaneously the variables of Store Atmosphere and product availability have a significant effect on on the purchase intention in Mandiri Mart Pekanbaru.. There are contribution the influence of Store Atmosphere and product availability on the purchase intention in the Mandiri Mart Pekanbaru of Obtained value of Adjusted R Square equal to 0,424 or 42,4% and 57,6 % influenced by the other factors that are not pursuing in this research. So this research to strengthen previous studies.